Techno-Economics of Solar Tunnel Dryer- A Case Study. - Seveda, M S; Rathore, N S; Singh, Pratap (Journal of Agricultural Engineering, 2004)
A solar tunnel dryer installed at M/S Phospate India Pvt. Limited has been evaluated in terms of its techno-economic analysis, which was carried out by using different economic indicators such as Net Present Worth (NPW), Benefit cost ratio and Pay back period and compared with electrical drying system. The net present worth (NPW) for commercial Solar tunnel dryer is Rs. 78,74,500 whereas for diesel fired electrical dryer it is Rs. 36,52,500. The benefit cost ratio for solar tunnel dryer and for the diesel fired electrical dryer is 7.08 ad 2.56 respectively. The total payback period for commercial solar tunnel dryer is 10 months, whereas it is 2.9 years for diesel fired electrical dryer.The economic of solar tunnel dryer was made in comparison with diesel fired electrical dryer, because initially company was having diesel fired dryer, before introduction of solar tunnel dryer. It was' observed that commercial solar tunnel dryer is a good proposition for drying of all kind of material and is techno-economically better than electrical drying system. Significant saving in electrical energy could be achieved through its use.